2018
DOI: 10.15761/orr.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Long term survival of patients with gastric cancer treated with adjuvant radio-chemotherapy: proposal of a prognostic index with implication for treatment modification

Abstract: Purpose/Objective (s): Definitive surgery followed by adjuvant radio chemotherapy has been the standard of care for patients with gastric cancer since the publication of INT0116 study in 2001. This study is to analyze the outcomes of patients with gastric cancer treated with adjuvant radio chemotherapy in Manitoba.Materials/Methods: After definitive surgical resection, patients with Stage IB to IVM0 gastric cancer were treated with fluorouracil (5-FU) and leucovorin. Radiotherapy with concomitant 5-FU was init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…There are evidences supporting that clinical researches are exploring the benefits of giving chemotherapy as adjuvant therapy for surgery to destroy remaining cancer cells 37 . In recent analyses of definitive surgery followed by adjuvant radio chemotherapy (5-Fu/leucovorin LV regimens) for patients with gastric cancer, Liu and Ahmed reported that 59.3% (48/81) patients survived >3 years, 18.5% (15/81) patients survived 5 or more years 38 . Eighteen out of 81(22.2%) patients are still alive with a medium survival of 142 months (57-196 months).…”
Section: Discussionmentioning
confidence: 99%
“…There are evidences supporting that clinical researches are exploring the benefits of giving chemotherapy as adjuvant therapy for surgery to destroy remaining cancer cells 37 . In recent analyses of definitive surgery followed by adjuvant radio chemotherapy (5-Fu/leucovorin LV regimens) for patients with gastric cancer, Liu and Ahmed reported that 59.3% (48/81) patients survived >3 years, 18.5% (15/81) patients survived 5 or more years 38 . Eighteen out of 81(22.2%) patients are still alive with a medium survival of 142 months (57-196 months).…”
Section: Discussionmentioning
confidence: 99%
“…The relative benefits of these different drugs, alone or in combination, are unclear [36].There are evidence supporting that clinical researches are exploring the benefits of giving chemotherapy as adjuvant therapy for surgery to destroy remaining cancer cells [37]. In recent analyses of definitive surgery followed by adjuvant radio chemotherapy(5-Fu/leucovorin LV regimens) for patients with gastric cancer, Liu and Ahmed [38] reported that 59.3%(48/81) patients survived > 3 years,18.5% (15/81) patients survived 5 or more years. Eighteen out of 81(22.2%) patients are still alive with a medium survival of 142 months (57-196 months).…”
Section: Discussionmentioning
confidence: 99%
“…But unfortunately, up to 50% of patients have experienced tumor recurrence overthe first five years, which indicates that the results of surgery alone have been insufficient [14]. Additionally, radiation therapy and traditional postoperative chemotherapy have failed to work effectively in the case of GIST [15,16]. On the other hand, the treatment of GIST has been revolutionized by the introduction of smallmolecule kinase inhibitors that specifically target the underlying pathogenic mutant kinase.…”
Section: Introductionmentioning
confidence: 99%